2019
DOI: 10.1177/0003319719877096
|View full text |Cite
|
Sign up to set email alerts
|

Early Invasive Versus Ischemia-Guided Strategy in Non-ST-Segment Elevation Acute Coronary Syndrome With Chronic Obstructive Pulmonary Disease: A National Inpatient Sample Analysis

Abstract: Chronic obstructive pulmonary disease (COPD) is a risk factor for non-ST-segment elevation–acute coronary syndromes (NSTE-ACS). Whether early invasive strategy (EIS) or ischemia-guided strategy (IGS) confers better outcomes in NSTE-ACS with COPD is largely unknown. Nationwide Inpatient Sample database of the United States was queried from 2010 to 2015 to identify NSTE-ACS with and without COPD. Early invasive strategy was defined as coronary angiogram with or without revascularization on admission day 0 or 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We read the article entitled “Early Invasive Versus Ischemia-Guided Strategy in Non-ST-Segment Elevation Acute Coronary Syndrome With Chronic Obstructive Pulmonary Disease: A National Inpatient Sample Analysis” with interest. 1 The authors evaluate the intervention strategy in non-ST-segment elevation acute coronary syndrome (NSTE-ACS) patients with chronic obstructive pulmonary disease (COPD) and without COPD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read the article entitled “Early Invasive Versus Ischemia-Guided Strategy in Non-ST-Segment Elevation Acute Coronary Syndrome With Chronic Obstructive Pulmonary Disease: A National Inpatient Sample Analysis” with interest. 1 The authors evaluate the intervention strategy in non-ST-segment elevation acute coronary syndrome (NSTE-ACS) patients with chronic obstructive pulmonary disease (COPD) and without COPD.…”
mentioning
confidence: 99%
“…In addition, COPD is a risk factor for complex CAD, and only forced expiratory volume 1 (FEV1) is negatively correlated with SYNTAX score. 4 Ando et al 1 showed that NSTE-ACS patients were not systematically tested for the presence of COPD. How did these researchers diagnose COPD anddo they have basal FEV1, forced vital capacity (FVC), total lung capacity (TLC), and functional residual capacity FRC values?…”
mentioning
confidence: 99%